Beban Kerja Mental menurut Level Jabatan dan Usia Karyawan di IndustriCPO - Syamsul Anwar; Deli Mutiara (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
Mental workload represents the level of a person's mental needs of the job demands. The level of mental workload can be different for every individu that is caused by various factors. This research aimed to investigated mental workload of employees according to job level positionand employees’ age, and to identified the contributors of mental workload. The study was conducted on employees in a palm oil mill. Mental workload of employees was measured by subjective approach through NASA-Task Load Index (TLX) method. The main data was collected by interview and NASA-TLX questionnaire. There were 31 employees who participated to this study. The analysis was carried outbydescriptive and statistical approach. The descriptive analysis presentedthat employees ofhigher job level positionhave higher mental workload than employees of lower job level. The analysis of variance result indicated a significant difference of mental work load among job level positions. Descriptive analysis indicated mental workload increased accord to age group. The correlation and regression analysis indicated that emloyees’ age had strong relationship and significantly affected to mental workload. The greatest contributors to mental work load level on the lower job level position were physical demand and effort, meanwhile on relatively higher job level positionwas temporal demand.Key words: age of employee , job level, mental work load